Perfil oxidativo e atividade da enzima delta-aminolevulinato desidratase em gestantes saudáveis e em gestantes com pré-eclâmpsia - Lucca, Leidiane de (2016)
During pregnancy, even being a physiological process, there is an increase in oxidative stress due to increased metabolic demands and increased oxygen consumption in the tissues, especially in the placenta, in response to fetal growth and maternal physiological changes. Furthermore, due to the increased maternal demands for the development of the fetus, iron deficiency can also occur during pregnancy, being then indicated supplementation with this compound because its absence may cause anemia, and generate an increased oxidative stress in pregnant women. Another gestational pathology that is also involved in increased oxidative stress is preeclampsia, which is characterized by increased blood pressure and proteinuria in pregnant women, it has unknown etiology and is the leading cause of maternal and fetal morbidity. Oxidative stress is involved in the pathophysiology of this disease, damaging macromolecules such as DNA, lipids and proteins. The sufhydryl delta-aminolevulinate dehydratase enzyme (δ-ALA-D) can be inhibited by pro-oxidants situations and such inhibition results in the accumulation of 5-aminolevulinic acid, it is directly related to increased production of free radicals, and therefore,the enzyme δ-ALA-D can be suggested as an indirect marker of oxidative stress. Considering that oxidative stress is directly involved in pregnancy pathologies, the aim of this study was to evaluate oxidative profile and δ-ALA-D activity in pregnant women with and without iron supplementation and in pregnant women with preeclampsia. Oxidative stress parameters were analyzed by quantification of reactive species thiobarbituric acid (TBARS), the protein thiol groups (P-SH) and no protein (NP-SH), levels of vitamin C, in addition to determining the activity of enzymes catalase and δ-ALA-D in healthy women with and without supplementation with iron and in pregnant women with preeclampsia. The TBARS levels were significantly higher in pregnant women without iron supplementation, and pregnant women with preeclampsia, while the antioxidant system of the same appears to be reduced due to a reduction in the levels of P-SH, NP-SH and vitamin C, as well as decrease in the activity of catalase and δ-ALA-D enzymes. Based on these results, we conclude that iron supplementation can cause a protective effect to the oxidative damage caused by pregnancy when compared to pregnant women without supplementation. Furthermore, there is an increased state of oxidative stress and decrease in the δ-ALA-D activity in women with preeclampsia when compared to healthy pregnant women, and it may be involved in the complications of this disease and quantification of the activity of this enzyme may be useful in assessing the damage caused by preeclampsia.